Texas Women : Their Histories, Their Lives - Turner, Elizabeth Hayes (Book collections on Project MUSE., 2015)
"Texas Women : Their Histories, Their Lives engages current scholarship on women in Texas, the South, and the United States. It provides insights into Texas's singular geographic position, bordering on the West and sharing a unique history with Mexico, while analyzing the ways in which Texas stories mirror a larger American narrative. The biographies and essays illustrate an uncommon diversity among Texas women, reflecting experiences ranging from those of dispossessed enslaved women to wealthy patrons of the arts. That history also captures the ways in which women's lives reflect both personal autonomy and opportunities to engage in the public sphere. From the vast spaces of northern New Spain and the rural counties of antebellum Texas to the growing urban centers in the post-Civil War era, women balanced traditional gender and racial prescriptions with reform activism, educational enterprise, and economic development. Contributors to Texas Women address major questions in women's history, demonstrating how national and regional themes in the scholarship on women are answered or reconceived in Texas. Texas women negotiated significant boundaries raised by gender, race, and class. The writers address the fluid nature of the border with Mexico, the growing importance of federal policies, and the eventual reforms engendered by the civil rights movement. From Apaches to astronauts, from pioneers to professionals, from rodeo riders to entrepreneurs, and from Civil War survivors to civil rights activists, Texas Women is an important contribution to Texas history, women's history, and the history of the nation"--